THE CONSEQUENCES OF SOCIAL MEDIA AND SOCIAL SOCIALIZATION AMONG YOUNG FOOTBALL PLAYERS: A COMPREHENSIVE RESEARCH STUDY - Arshed Dhafer Abdulsahib (Proximus Journal Publishing, 2025)
This research investigates how using social media and socializing with other young football players at the Diwaniya Club in Iraq affects them. The study's goal is to find out how the pros and cons of using social media are related to the pros and cons of socializing with other people on the team. Using a quantitative descriptive method, data were gathered from 23 young players using a validated questionnaire that looked at four primary factors: the good and bad effects of social media, the strength of social socialization, and the weakness of social socialization. We used SPSS to do statistical analysis that included descriptive statistics, Pearson correlation analysis, and reliability testing using Cronbach's Alpha. The results showed a high positive link (r=0.879, p
Keywords: Social Media; Social Socialization; Youth Football